2016
DOI: 10.1039/c6ra23075j
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of two novel functional metal–organic microcapsules; an investigation into ligand expansion effects on the metal–organic microcapsules' properties

Abstract: Effects of ligand expansion on the size, morphology and loading capacity of tetrazole-based metal–organic microcapsules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…All this while, SEM and TEM images of the synthesized CMNPs/1,4-Zbtbs by using ultrasonic irradiation revealed that CMNPs encapsulation was successfully done in very short time, which agrees well with our previous studies (Fig. 3 and S1 ) [43] , [44] , [45] . In addition, vibrating-sample magnetometer (VSM) was employed for investigation of magnetic properties of CMNPs/1,4-Zbtb composite.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…All this while, SEM and TEM images of the synthesized CMNPs/1,4-Zbtbs by using ultrasonic irradiation revealed that CMNPs encapsulation was successfully done in very short time, which agrees well with our previous studies (Fig. 3 and S1 ) [43] , [44] , [45] . In addition, vibrating-sample magnetometer (VSM) was employed for investigation of magnetic properties of CMNPs/1,4-Zbtb composite.…”
Section: Resultssupporting
confidence: 92%
“…So, our optimized catalyst was CMNPs/1,4-Zbtb and specific characterization about it was carried out. It should also be noted that due to the high structural similarities of the two ICPs, almost identical results in early characterization are not unexpected, although full characterization about Fe 3 O 4 /1,3-Zbtb was carried out in our previous work [43] , [44] , [45] . Powder x-ray diffraction (PXRD) pattern was used first as direct evidence to confirm the formation of CMNPs/1,4-Zbtb.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…Tetrazolate-derived ligands represent one of the most complex nitrogen-rich ligand classes with regard to their coordination ability and charge flexibility, which leads to a variety of coordination modes. Herein, as shown in Figure , Na 2 (dtp)·2H 2 O (H 2 dtp = 2,3-di-1 H -tetrazol-5-ylpyrazine) and Na­(H 2 ibt)·3H 2 O [H 3 ibt = 4,5-bis­(tetrazol-5-yl)­imidazole] are chosen to synthesize lanthanide compounds and further used for lanthanide separation due to their facile synthesis, stability and safety, , wide diversity of potential coordination modes (the details are shown in Scheme S1), and high solubility in water. Lanthanide compounds containing anions of the tetrazole-containing ligands, Na 2 (dtp)·2H 2 O and Na­(H 2 ibt)·3H 2 O, have been synthesized by salt metathesis (Scheme ).…”
Section: Introductionmentioning
confidence: 99%